Management of Scouting Education in Shaping Nationalism and Patriotism Attitudes of Students at the 209-210 Scout Unit of MAS Madinatussalam - Fifah, Khofifah; Ramadhani, Putri Suci; Wardani, Tika Kesuma; Sembiring, Desi Fitri Yani; Masliani, Desi; Budi, Budi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study examines the management of scouting education in shaping the nationalism and patriotism attitudes of students at the 209-210 Scout Unit of MAS Madinatussalam. Using a qualitative method with a case study approach, this research analyzes the processes of planning, implementation, and evaluation of scouting programs. The results show that activities such as camping, flag ceremonies, and drill training are effective in instilling national values. Scout leaders play a strategic role in integrating nationalism content, building motivation, and ensuring the achievement of character-building goals. This study concludes that the management of scouting education has a positive impact on fostering nationalism and patriotism attitudes in students.